Adaptive optics effect on performance of BPSK-SIM oceanic optical wireless communication systems with aperture averaging in weak turbulence. (November 2020) - Gökçe, Muhsin Caner; Baykal, Yahya; Ata, Yalçın
Highlights: An OOWC system employing aperture averaging and Gaussian beam is considered. Binary phase shift-keying subcarrier intensity modulation is used to modulate the Gaussian laser. Effects of adaptive optics on BER performance of the OOWC system operating in weak oceanic turbulence are investigated. BER performance of the OOWC system with adaptive optics is compared to that of the OOWC system without adaptive optics. Abstract: Turbulence-induced wavefront deformations cause the irradiance of an optical signal to fluctuate resulting a in serious degradation in the bit-error-rate (BER) performance of optical wireless communication (OWC) system. Adaptive optics is an effective technique to compensate for the wavefront aberrations to reduce the fluctuations in the received intensity. In this paper, we investigate how the adaptive optics technique affects the BER performance of an oceanic OWC (OOWC) system employing binary phase shift keying-subcarrier intensity modulation (BPSK-SIM) and aperture averaging. To evaluate BER performance in weak oceanic turbulence, the required entities such as the received optical power captured by a circular aperture and the aperture averaged scintillation index measuring the fluctuations in the received irradiance are derived. The effect of adaptive optics correction of various wavefront aberrations (i.e., tilt, defocus, astigmatism and the coma) on the BER performance is illustrated and the performance of the adaptive optics-OOWC system is compared to that of a non-adaptive optics OOWC system by the metric defined.